2020
DOI: 10.4269/ajtmh.20-0040
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear and Threshold Effect of Meteorological Factors on Japanese Encephalitis Transmission in Southwestern China

Abstract: Although previous studies have reported that meteorological factors might affect the risk of Japanese encephalitis (JE), the relationship between meteorological factors and JE remains unclear. This study aimed to evaluate the relationship between meteorological factors and JE and identify the threshold temperature. Daily meteorological data and JE surveillance data in Dazhou, Sichuan, were collected for the study period from 2005 to 2012 (restricting to May-October because of the seasonal distribution of JE). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…According to the model outputs, vector carrying capacity, weather variations, human-induced environmental discharges, and geographic location significantly impact vector and animalreservoir abundance. Geographic and temporal variations have also been incorporated in other models to understand variations in mosquito-borne diseases (Caldwell et al 2021), and human JE cases have been linked to changes in meteorological factors such as daily rainfall (Liu et al 2020). Models incorporating environmental drivers of JEV transmission, particularly climate features, might more accurately predict JE occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…According to the model outputs, vector carrying capacity, weather variations, human-induced environmental discharges, and geographic location significantly impact vector and animalreservoir abundance. Geographic and temporal variations have also been incorporated in other models to understand variations in mosquito-borne diseases (Caldwell et al 2021), and human JE cases have been linked to changes in meteorological factors such as daily rainfall (Liu et al 2020). Models incorporating environmental drivers of JEV transmission, particularly climate features, might more accurately predict JE occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…China is one of the most vulnerable countries with respect to climate change [11]. Many studies have found the significant positive relationship between weather conditions and vector-borne diseases in China, including the effects of meteorological factors, such as temperature, precipitation, humidity, wind speed [12][13][14][15][16][17], and extreme weather events (e.g., extremely high temperatures, extremely high rainfall, and tropical cyclones) [18][19][20][21][22][23][24]. The 2020 China Report of the Lancet Countdown on Health and Climate Change showed that China's climate suitability for mosquito-borne dengue fever has increased by 37% in the past half century [25].…”
Section: Introductionmentioning
confidence: 99%